Reliability and validity of European Quality of Life 5 Dimension (EQ-5D) for measuring health-related quality of life in knee osteoarthritis patients at Cipto Mangunkusumo General Hospital - Pramono, A; Sumariyono, Sumariyono; Isbagio, Harry (Indonesian Journal of Rheumatology, 2010)
Background: Quality of life is very important to knee osteoarthritis (OA) patients. The term quality of life denotes one that is health-related. One of the questionnaires most frequently used to measure the quality of life is the European Quality of Life 5-Dimension (EQ-5D) questionnaire. At Cipto Mangunkusumo General Hospital, until today there has not been any instrument for measuring the health-related quality of life in knee OA patients that has been tested for its reliability and validity.Objective: To prove the reliability and validity of EQ-5D as a measurement tool inÂ  determining the healthrelated quality of life in knee OA patients at Cipto Mangunkusumo General Hospital.Methods: This is a validity study in which all patients were asked to complete both the EQ-5D form and 36- item short form (SF-36) on their fi rst visit. They were subsequently asked again to complete only the EQ-5Dform one week after their fi rst visit.Results: Data were obtained from 86 respondents.The value of the intraclass correlation coeffi cient of each EQ-5D dimension, EQ-5D index, and visual analogue scale (VAS) was excellent (>0.75). Cronbachâs Î± value for internal consistency reliability in this study was0.6772 (<0.7). The external validity of EQ-5D compared to SF-36 was analyzed with the Pearsonâs correlation test and revealed a signifi cant correlation (p<0.01) of all EQ-5D dimensions, EQ-5D index, and EQ-5D VAS with total score of SF-36 except for the dimensions of self-care, pain, and anxiety/depression. The construct validity of EQ-5D showed that all of the dimensions were signifi cantly correlated with the EQ-5D index (p<0.01) except for self-care dimension.Conclusion: EQ-5D is a valid and reliable measurement tool. It is thus recommended for measuring the healthrelated quality of life in knee OA patients at CiptoMangunkusumo General Hospital.